GROWTH, BODY COMPOSITION AND PHYSICAL FITNESS IN SCHOOLCHILDREN AMAZONENSES, BRAZIL (Fiep Bulletin - online, 2014)
The objective of the study was to investigate the profile of the growth indicators and the behavior of the variables of the physical fitness related to the health, through a traverse approach using a battery of tests of motor acting and of the measures anthropometrics. It was studied a sample of 3.878 subject of both sexes with age among seven to 10 years, selected schoolchildren of the municipal public net of the municipal district randomly in population of Manaus-AM. The results of the variables anthropometrics of the present study between boys and girls indicated there to be differences significant estatisticament in the girls benefit in the stature variables and cutaneous folds and that the same ones are on average more discharges and heavier. As for the comparison of the results in the variables of motor acting the information significant differences were verified in the boys benefit in all of the ages in you pierced them of modified sit-up and in the 9 minutes run/walk and in almost all of the ages in the test to seat-and-reach.
Keywords: Growth; Physical fitness; body composition